Urdu class 7 - Dr mehmood ahmed kawish (Chaudry ghulam rasool and sons Lahore, 2012)
Urdu Class 7 provides a foundational introduction to the Urdu language, focusing on vocabulary, grammar, and basic reading and writing skills for young learners.